AAP issues guidance to EDs on acute pediatric mental health conditions. Issue 10 (October 2016) - Knopf, Alison
Abstract : The American Academy of Pediatrics (AAP) last month issued a call for emergency department (ED) clinicians to pay attention to pediatric patients with acute mental health or behavioral problems. The report came in two parts, one devoted to common clinical challenges and the other to side effects of psychiatric medications that may not be known to ED clinicians, as well as problems with diagnosis of somatic conditions.